An analysis of International legal documents and national legal acts of the Republic of Kazakhstan in the sphere of tourism activity - Bahadır Erdem, B.; Kala, N.S. (KSU Publ., 2016)
Nowadays tourism has become one of the leading sectors of the world economy. Development of tourism is a priority direction in Kazakhstan’s policy. Intergovernmental cooperation in the tourism sphere is regulated and organized by bilateral and multilateral international treaties. Thus, this article aims to examine international legal acts and national legislation in the Republic of Kazakhstan in tourism sector, to analyze bases of cooperation of states in the sphere of international tourism. Moreover, an activity of the World Tourism Organization, fundamental principles of tourism established in international law documents, are analyzed, too.
Қазақстан Республикасының туристік қызмет аясындағы халықаралық- құқықтық құжаттарын жəне ұлттық құқықтық актілерін талдау
Анализ международно-правовых документов и национальных правовых актов Республики Казахстан в сфере туристской деятельности
Keywords: tourism; international law; national legal acts; law; principles; convention; declaration